2005
DOI: 10.1111/j.1365-2559.2005.02161.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour budding as prognostic factor in stage I/II colorectal carcinoma

Abstract: This study confirms the prognostic value of budding in a contemporary series of colorectal carcinomas that by TNM were low risk. Technically easy, rapid and robust to determine, budding quantified in pan-cytokeratin stains significantly aids in the identification of high-risk patients and is recommended for more general use in surgical pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
199
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(209 citation statements)
references
References 11 publications
7
199
1
2
Order By: Relevance
“…In one of the earlier studies of tumor budding, Hase et al 18 demonstrated that 5-year survival rates of Dukes B (stage II, T3-4 N0) patients with high-grade budding are significantly worse than those of Dukes C (N þ ) patients without budding (29 percent vs 66 percent; Po0.001). A number of more recent studies have confirmed that patients with Stage II colorectal carcinoma do significantly worse when high-grade budding is present, [34][35][36]38,41,45 and several studies have shown that survival rates of patients with Stage II colorectal carcinoma with high-grade budding are equivalent to survival rates of patients with Stage III colorectal carcinoma. [34][35][36] In their studies of Stage II and III pT3 tumors, Okuyama et al 34,35 found that tumor budding was the only factor on multivariate analysis to be associated with decreased survival and was more prognostically significant than lymph node metastases.…”
Section: Tumor Budding In Stage II (T3-4 N0) Colorectal Carcinomamentioning
confidence: 95%
See 4 more Smart Citations
“…In one of the earlier studies of tumor budding, Hase et al 18 demonstrated that 5-year survival rates of Dukes B (stage II, T3-4 N0) patients with high-grade budding are significantly worse than those of Dukes C (N þ ) patients without budding (29 percent vs 66 percent; Po0.001). A number of more recent studies have confirmed that patients with Stage II colorectal carcinoma do significantly worse when high-grade budding is present, [34][35][36]38,41,45 and several studies have shown that survival rates of patients with Stage II colorectal carcinoma with high-grade budding are equivalent to survival rates of patients with Stage III colorectal carcinoma. [34][35][36] In their studies of Stage II and III pT3 tumors, Okuyama et al 34,35 found that tumor budding was the only factor on multivariate analysis to be associated with decreased survival and was more prognostically significant than lymph node metastases.…”
Section: Tumor Budding In Stage II (T3-4 N0) Colorectal Carcinomamentioning
confidence: 95%
“…Similarly, the presence of budding has been associated with increased risk of distant metastases, [34][35][36] suggesting that budding may also be associated with vascular invasion. A few tumor-budding studies have used vascular markers and/or elastic stains to assess vascular invasion, 11,12,19,22,26,32,37,38 but only four have analyzed the relationship between budding and vascular invasion: Kazama et al 22 found no relationship between budding and vascular invasion, whereas three other studies have reported a statistically significant correlation between budding and venous invasion, though the association was not as pronounced as the relationship with lymphatic invasion and lymph node metastases. 11,12,32 The tumor-host interaction at the invasive front may be of prognostic importance in the setting of tumor budding.…”
Section: Morphological Featuresmentioning
confidence: 99%
See 3 more Smart Citations